Effects of autotoxicity and allelopathy on seed germination and seedling growth in Medicago truncatula - Wang, Chang; Liu, Zhe; Wang, Zicheng; Pang, Wenhui; Zhang, Long; Wen, Zhaozhu; Zhao, Yiran; Sun, Juan; Wang, Zeng-Yu; Yang, Chao (Frontiers in Plant Science, 2022)
Autotoxicity is a form of intraspecific allelopathy in which a plant species inhibits the establishment or growth of the same species through the release of toxic chemical compounds into the environment. The phenomenon of autotoxicity in crops is best traced in alfalfa (Medicago sativa).. A close relative of alfalfa, M. truncatula, has been developed into an excellent model species for leguminous plants. However, it is not known whether M. truncatula has autotoxicity. In this study, M. truncatula root exudates showed negative impact on the growth of M. truncatula seedlings, indicating autotoxicity. Detailed analyses with plant extracts from M. truncatula and alfalfa revealed varying degrees of suppression effects in the two species. The extracts negatively affected seed germination potential, germination rate, radicle length, hypocotyl length, syntherical allelopathic effect index, plant height, root growth, fresh weight, dry weight, net photosynthetic rate, transpiration rate and stomatal conductance in both M. truncatula and alfalfa. The results demonstrated, that autotoxicity and allelopathic effects exist in M. truncatula. This opens up a new way to use M. truncatula as a model species to carry out in-depth studies of autotoxicity and allelopathy to elucidate biochemical pathways of allelochemicals and molecular networks controlling biosynthesis of the chemicals.